Modeling ecodevelopmental context of sexually transmitted disease/HIV risk and protective behaviors among African-American adolescents - Li, Ya-Huei (HIV AIDS (Auckl), 2017)
Risk and protective processes are integrated developmental processes that directly or indirectly affect behavioral outcomes. A better understanding of these processes is needed, in order to gauge their contribution to sexual risk behaviors. This retrospective cross-sectional study modeled the ecodevelopmental chain of relationships to examine the social contexts of African-American (AA) adolescents associated with sexually transmitted disease (STD)- and HIV-risk behaviors. We used data from 1,619 AA adolescents with an average age of 16±1.8 years obtained from the first wave of the National Longitudinal Study of Adolescent Health for this study. Confirmatory factor analysis followed by structural equation modeling was conducted to identify the latent constructs that reflect the social–interactional components of the ecodevelopmental theory. Among contextual factors, findings indicated that a feeling of love from father, school, religion, and parent attitudes toward adolescent sexual behavior were all factors that played significant roles in the sexual behavior of AA adolescents. AA adolescents who reported feeling love from their father, feeling a strong negative attitude from their parents toward having sex at a very young age, and having a strong bond with school personnel were associated with better health statuses. The level of parents’ involvement in their children’s lives was reflected in the adolescents’ feeling of love from parents and moderated by their socioeconomic status. Being male, attaining increased age, and being a sexual minority were associated with higher likelihood of exhibiting risky sexual behavior. In contrast, higher socioeconomic status and fathers’ level of involvement were indirectly associated with reduced STD/HIV-related sexual risk behavior. In conclusion, our findings suggest that interventions aimed at maximal protection against STD/HIV-related risk behavior among AA adolescents should adopt both self- and context-based strategies that promote positive functioning in the family, school, and peer microsystems.